Alootook Ipellie: The Voice of an Inuk Artist - Kennedy, Michel (Studies in Canadian Literature, 1996)
Because he is "living between cultures," Alootook Ipellie, the poet, cartoonist, columnist, and editor of Inuit Today, attempts to focus his work on the reality of the events that are happening in the Arctic, "speaking to both sides at the same time." Although he has moved from his Baffin Island homeland to larger cities such as Iqaluit and Ottawa, he always has an urge to go back to the land. In his poetry, the land helps to interpret some of the old ways of the people.